Neuroprotektive Wirkung von Sideritis scardica Griseb. in Caenorhabditis elegans als Modellorganismus für neurodegenerative Erkrankungen - Heiner, Felix (Universitätsbibliothek Heidelberg, 2020)
Sideritis scardica Griseb., also known as Greek mountain tea, is a plant that belongs to the family of Lamiaceae. It is endemic to the Balkan region, where the herb is traditionally used against a broad range of afflictions, mostly as an infusion. Over the past few years, S. scardica has been scientifically investigated for the pharmacological properties it is said to have, especially focusing on the effects in the central nervous system, such as an improved cognitive performance and the reduction of β-amyloid plaques which are typical in Alzheimer's disease. Following this issue, the main goal of the present study was to examine whether extracts of Greek mountain tea counteract further pathomechanisms of this and other neurodegenerative disorders which are a rising health concern in our ageing society. For this purpose six hydroalcoholic S. scardica extracts of different lipophilicity, that were produced and phytochemically analysed by Finzelberg GmbH & Co. KG, were investigated for their neuroprotective activity in the model organism Caenorhabditis elegans. Additionally, six fractions of one of the most potent extracts, seven isolated pure compounds and extracts of some well-known medicinal plants were tested. The mid-polar extracts of S. scardica in particular, as well as the more lipophilic fractions and the phenylethanoid glycosides, were counteracting the aggregation or toxicity of β-amyloid peptides, α-synuclein, 6-hydroxydopamine, tau- and polyglutamine proteins in vivo, whereas they did not reveal any antioxidant properties in the nematodes. The spectrum of activities of S. scardica was especially comparable with that of Bacopa monnieri (Brahmi), a plant used in ayurvedic medicine. The alleviation of the neurotoxicity of the proteins and compounds make S. scardica extracts interesting for the preventive or therapeutic treatment of Alzheimer's, Parkinson's, Huntington's and other neurodegenerative diseases. The phenylethanoids could be identified as active constituents, although synergistic effects between extractives of different polarity remain probable and have to be taken into consideration. Also, a hypothetical mode of action could be postulated: the bonding of polyphenols to the peptides, directly inhibiting their aggregation to toxic oligomers or plaques and fibrils. In the present study, the activity of hydroalcoholic Sideritis scardica extracts against hallmarks of Alzheimer's disease could be affirmed and for the first time, positive effects on further neurotoxic substances could be shown, expanding the neuropharmacological profile of the Greek mountain tea. As some studies on vertebrates and humans assessing the influence on cognitive performance and proving the harmlessness have already been conducted, high-quality clinical studies investigating the preventive or therapeutic efficacy against Alzheimer's etc. should be performed.
Keywords: Hochschulschrift